(untitled) (Research, Society and Development, 2022)
The Atlantic Forest is a biodiversity hotspot, with one of its last large forests located in Serra do Japi, in an urbanized region of the state of São Paulo. To protect this forest, in 1984 the Cajamar, Cabreúva and Jundiaí Environmental Protection Area (APAs CCJ) was established, regulated in 1998 and expanded in 2006. The study characterized the forest cover of the APAs CCJ, qualifying the patches by applying a Forest Quality Index (IQF), composed of landscape metrics AREA, IC, ENN and PROXRIO. Secondary data processed in a Geographic Information System (GIS) was used. The landscape has a forest cover of 35.25%, predominating patches of up to 10 hectares, representing 85.46% of the fragments. Forest cover is unevenly distributed, with the largest patches concentrated in the Serra do Japi region, and with forest cover below 30% in watershed areas. The average distance between the patches, and between these and the hydrography, is less than 60 meters, resulting in a good IQF score for 88.64% of the forests. Small patch suppression scenarios increase the mean distance between patches more than in large patch suppression scenarios, indicating that small patches are important in landscape connectivity. It is concluded that the environmental quality of forest fragments in the landscape is good, and that the regulation of APAs CCJ should increase the protection of small forest patches, in addition to the ecological restoration of strategic areas, aiming at the conformation of corridors between the fragments.